Mutations in the promoter region of the gene for gp91-phox in X-linked chronic granulomatous disease with decreased expression of cytochrome b558. - Newburger, P E (1994)
We examined the molecular defect in two kindreds with "variant" X-linked chronic granulomatous disease (CGD). Western blots of neutrophil extracts showed decreased immunoreactive cytochrome b558 components gp91-phox and p22-phox. Analysis of mRNA demonstrated reduced gp91-phox transcripts, with relative preservation of an alternative mRNA species created by transcription initiation in the third exon of the gene. Single strand conformation polymorphism analysis of the 5' flanking region of the patients' gp91-phox genes revealed an electrophoretic abnormality not detected in 40 other gp91-phox genes. Genomic sequencing demonstrated a single base change associated with CGD in each kindred: in one, adenine to cytosine at base pair-57 and in the other, thymidine to cytosine at -55. These mutations are located between the "CCAAT" and "TATA" box consensus sequences involved in eukaryotic gene transcription. Gel shift assays revealed two specific DNA-protein complexes formed between phagocyte nuclear extracts and an oligonucleotide probe representing bases -31 to -68 of the gp91-phox promoter region; the faster-migrating complex could not be formed with oligonucleotides containing either of the promoter mutations. Thus, these promoter region mutations appear to be causally related to the loss of association of a DNA-binding protein and lead to diminished gp91-phox expression, abnormal transcription initiation, and the development of CGD.